The combination of chitosan and molasses to improve nutritive value, chemical quality, and in vitro rumen degradability of pineapple peel silage - RAKHMAD PERKASA HARAHAP; YETI ROHAYETI; DUTA SETIAWAN; AGUSTIN HERLIATIKA; YENI WIDIWATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Harahap RP, Rohayeti Y, Setiawan D, Herliatika A, Widiwati Y. 2024. The combination of chitosan and molasses to improve nutritive value, chemical quality, and in vitro rumen degradability of pineapple peel silage. Biodiversitas 25: 2800-2810. This study aimed to evaluate and determine nutritive value, chemical silage quality, in vitro rumen fermentation profile, microbial population, digestibility, and methane (CH4) emission of pineapple (Ananas camosus L.) peel silage with the addition of chitosan and molasses. The experiment was carried out using a 2×3 factorial design with 6 treatments, 4 replications, and different in vitro runs acting as blocks. In addition, the treatments comprised control (no additives), C3 (3 g of chitosan per 1000 g of fresh pineapple peel), C5 (5 g of chitosan per 1000 g of fresh pineapple peel), M20 (20 g of molasses per 1000 g of pineapple peel), C3M20 (3 g of chitosan and 20 g of molasses per 1000 g of pineapple peel), and C5M20 (5 g of chitosan and 20 g of molasses per 1000 g of pineapple peel). The descriptive analysis results for nutritive value showed that the 5 g chitosan group had the highest dry matter (DM) content in pineapple peel silage after 21 days. Chitosan was shown to improve organic matter (OM) and crude protein (CP) levels while reducing hemicellulose content. The administration of molasses significantly reduced weight loss and pH, enhancing preservation quality (P<0.05). The results also showed that chitosan reduced weight loss, particularly at 5 g/kg fresh pineapple peel (P<0.05). Rumen fermentation analysis revealed higher acetic acid levels in silage without molasses (P<0.05), while pH, ammonia (NH3), propionic acid, butyric acid, and branched-chain volatile fatty acid (BCVFA) concentrations did not affect rumen fermentation (P>0.05). However, chitosan increased in vitro dry matter digestibility (IVDMD) and reduced total gas production (P<0.05). Higher levels also reduced microbial and protozoa populations in rumen. Based on the results, the use of both additives improved the quality of silage, where chitosan increased IVDMD and reduced gas production during rumen in vitro fermentation.